Dietary Milk Sphingomyelin Prevents Disruption of Skin Barrier Function in Hairless Mice after UV-B Irradiation - Oba, Chisato; Morifuji, Masashi; Ichikawa, Satomi; Ito, Kyoko; Kawahata, Keiko; Yamaji, Taketo; Asami, Yukio; Itou, Hiroyuki; Sugawara, Tatsuya (PloS one, 2015)
Exposure to ultraviolet-B (UV-B) irradiation causes skin barrier defects. Based on earlier findings that milk phospholipids containing high amounts of sphingomyelin (SM) improved the water content of the stratum corneum (SC) in normal mice, here we investigated the effects of dietary milk SM on skin barrier defects induced by a single dose of UV-B irradiation in hairless mice. Nine week old hairless mice were orally administrated SM (146 mg/kg BW/day) for a total of ten days. After seven days of SM administration, the dorsal skin was exposed to a single dose of UV-B (20 mJ/cm2). Administration of SM significantly suppressed an increase in transepidermal water loss and a decrease in SC water content induced by UV-B irradiation. SM supplementation significantly maintained covalently-bound ω-hydroxy ceramide levels and down-regulated mRNA levels of acute inflammation-associated genes, including thymic stromal lymphopoietin, interleukin-1 beta, and interleukin-6. Furthermore, significantly higher levels of loricrin and transglutaminase-3 mRNA were observed in the SM group. Our study shows for the first time that dietary SM modulates epidermal structures, and can help prevent disruption of skin barrier function after UV-B irradiation.